Combined application of entomopathogenic nematodes and fungi against fruit flies, Bactrocera zonata and B. dorsalis (Diptera: Tephritidae): laboratory cups to field study. Issue 7 (20th May 2022) - Wakil, Waqas; Usman, Muhammad; Piñero, Jaime C; Wu, Shaohui; Toews, Michael D; Shapiro‐Ilan, David I
Abstract: BACKGROUND: The peach fruit fly, Bactrocera zonata, and the Oriental fruit fly, B. dorsalis (Diptera: Tephritidae), are economically important fruit fly species in various regions of the world. We evaluated the effects of separate and combined applications of the entomopathogenic fungi (EPF) Beauveria bassiana (WG‐18) and Metarhizium anisopliae (WG‐02), and the entomopathogenic nematodes (EPNs) Heterorhabditis bacteriophora (VS strain) and Steinernema carpocapsae (ALL strain) against larvae, pupae and pharate adults, of B. zonata and B. dorsalis under laboratory, glasshouse and field cage conditions. RESULTS: Combined applications of EPF and EPNs produced greater mortality than individual treatments under all conditions. Against both species, the combination of B . bassiana and H. bacteriophora consistently exerted strong effects that were similar to the combined application of B. bassiana and S. carpocapsae whereas M. anisopliae applied with S. carpocapsae was least effective in all combinations. In a laboratory bioassay, synergistic interactions were detected between B. bassiana and H. bacteriophora applied against larvae and pharate adults of both fly species, between B. bassiana and S. carpocapsae against larvae of both species and pharate adults of B. zonata, and between M. anisopliae and H. bacteriophora against B. zonata larvae. Other combined treatments resulted in additive effects, especially against fly pupae. In a potted soil bioassay, there were only additive interactions in all combinations against different stages of both flies. The 3rd instar of both flies was more susceptible than pharate adult and pupal stages. Additive interactions between EPNs and EPF were detected in the glasshouse against 3rd instars and pupae, and under field conditions against 3rd instars of both fly species. CONCLUSION: These results indicate how particular combinations of entomopathogenic fungi and nematodes could be deployed in integrated pest management of tephritid fruit flies in orchard agro‐ecosystems. © 2022 Society of Chemical Industry. Abstract : The 3 rd instar of B. zonata and B. dorsalis was more susceptible than pharate adult and pupal stages in combined applications of EPF and EPNs.